Bioactive compounds and antibacterial activities in crystallized honey liquefied with ultrasound - Peláez-Acero, A. (Ultrason Sonochem, 2021)
The effect of ultrasound on the crystal size, phenols, flavonoids, Maillard products and antibacterial activity of crystallized honeys was studied. Three multifloral honeys (M), one monofloral (MO) and one honeydew (HD) honey were used. Ultrasound was performed at 42 kHz for different times (0, 5, 10 and 15 min). The antibacterial activities were tested against Salmonella typhimurium, Bacillus subtilis, Pseudomonas aeruginosa, Listeria monocytogenes, Staphylococcus aureus and Escherichia coli. In all honeys, the parameters analyzed had significant differences ((P < 0.05)). After 15 min of ultrasound the HD had increments of 44 mg of gallic acid/100 g of honey in phenols, and some M showed increase in flavonoids (5.64 mg of quercitin /100 g of honey) and improvement in inhibition against Salmonella typhimurium was 13.1%. In some honeys the correlation between phenols or flavonoids and antibacterial activity were significant ((P < 0.05)). No correlation was found between Maillard products and antibacterial activity. The ultrasound treatment effect on the crystal size, phenols, flavonoid, Maillard products, and antibacterial activity of crystallized honeys were different in each honey.